The Role of Muḥaddith in the History of Institutionalization of ‘Ulamā’ in the First Three Centuries of Islam - Kholili Badriza (El Tarikh : Journal of History, Culture and Islamic Civilization, 2025)
This research argues that Islam is an open religion by tracing the role of muḥaddith in the process of institutionalization of ʿulamāʾ in the first three centuries of Islam. The purpose of this research is to explain how Islamic openness is realized through the dynamics of the formation of hadith scientific networks and the process of scientific socialization carried out by muḥaddithūn in various early Islamic regions. This study uses historical methods (heuristic, criticism, interpretation and historiography) by analyzing 654 biographical entries in al-Ḏahabī Taḏkirat al-Ḥuffāẓ as the primary sources, and comparing them with a number of relevant classical and modern literature. The results of the study show that the role of muḥaddith is egalitarian and open to anyone, as seen in the pattern of transmission of ḥadīth, the spread of knowledge across regions, and the emergence of various maḏāhib and categories of knowledge. The conclusion of this study emphasizes that the diversity of Islamic traditions and science is an inherent characteristic of the openness of Islam. Implicitly, this study emphasizes the importance of understanding Islamic plurality as an epistemological foundation for the formation of a tolerant, inclusive, and dialogical scientific society.